Dynamics of Financial Streams of the Enterprise in System of Crisis Management - Leonid Valeryevich Domanskiy (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Resources of management of financial streams of the enterprise in system of crisis management are presented in article. The structure of management of financial streams of the organization concerning the center of the movement of financial means is considered. This approach is focused on the analysis of crisis management of the enterprises working in the conditions of market risks in particular risks of bankruptcy.